2012
DOI: 10.1007/s00018-012-0922-8
|View full text |Cite
|
Sign up to set email alerts
|

Airway basal cell vascular endothelial growth factor-mediated cross-talk regulates endothelial cell-dependent growth support of human airway basal cells

Abstract: Summary The human airway epithelium is a pseudostratified heterogenous layer comprised of ciliated, secretory, intermediate and basal cells. As the stem/progenitor population of the airway epithelium, airway basal cells differentiate into ciliated and secretory cells to replenish the airway epithelium during physiological turnover and repair. Transcriptome analysis of airway basal cells revealed high expression of vascular endothelial growth factor A (VEGFA), a gene not typically associated with the function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 50 publications
(77 reference statements)
0
35
0
Order By: Relevance
“…However, some ligands (FGF11-FGF14) do not bind FGFRs and have distinct modes of action (Olsen et al, 2003). Based on our prior work demonstrating crosstalk between endothelial cells and basal cells (Curradi et al, 2012), and the knowledge that FGF ligands play a role in regulating endothelial cell function, we assessed expression of FGF ligands in basal cells. RNA sequencing demonstrated that basal cells expressed only FGF2, FGF5, FGF11 and FGF13 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, some ligands (FGF11-FGF14) do not bind FGFRs and have distinct modes of action (Olsen et al, 2003). Based on our prior work demonstrating crosstalk between endothelial cells and basal cells (Curradi et al, 2012), and the knowledge that FGF ligands play a role in regulating endothelial cell function, we assessed expression of FGF ligands in basal cells. RNA sequencing demonstrated that basal cells expressed only FGF2, FGF5, FGF11 and FGF13 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Blocking of FGFR1 with a specific antibody suppresses endothelial-cell-dependent proliferation of basal cells Using our previously developed cytokine-and serum-free co-culture system, which utilizes modified primary human umbilical vein endothelial cells (HUVECs) constitutively expressing active Akt (HUVEC-Akt) (Curradi et al, 2012), we assessed the role of FGFR1-mediated signaling in regulating endothelial-cell-dependent proliferation of basal cells. Co-cultures of basal cells and endothelial cells were untreated, or incubated with control IgG or an antibody against FGFR1 (which blocks FGFligand-dependent signaling through this receptor) in the absence and presence of recombinant FGF2 or FGF5.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations